Challenging Underrepresentation of Women Leadership in Global South during COVID-19 - Laila Hanifah (Global South Review, 2020)
The WHO's analysis of gender equity in the health workforce of 104 countries has recorded that 70% of the global health workforce is women, while only 25% of them have the opportunity to be decision-makers in COVID-19 leadership. This large percentage has targeted women to be the majority group to get an infection exacerbated by fatigue and mental stress both in the workplace and family. The situation is worsened in Global South due to the low score of the global health system and a high gender gap that leads to inequality. Some important arguments reinforced why women's leadership during the crisis is matters and should be considered. This research will compare several case studies between Global North and Global South countries led by women and men as decision-makers in the COVID-19 pandemic case and in the end, these case studies would challenge women leadership in Global South. The success of the leadership parameter will be assessed from the total number of COVID-19 cases and total deaths from January 17th until October 21st, 2020. The findings found that the underrepresentation of women as decision-makers and policies in COVID-19 leadership led to the length of pandemic management and an increase in the number of COVID-19 cases in the Global South. In further explanation, the research identified several significant factors that explain why women leadership could be more successful to overcome the COVID-19 pandemic in Global South.